José Francisco Ruiz Casanova, Anthologos: poética de la antología poética. Cátedra, Madrid, 2007; 346 pp. - Torres de la Rosa, Danaé (El Colegio de México, 2010)
Se reseña el libro:Anthologas: poética de la antología poética.